Field notes contributed by Bery Engebretsen, December 1, 1991 - Engebretsen, Beryet al (1991)
List of birds and locations contributed by Bery Engebretsen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed/flatbed